MENGINTEGRASIKAN NILAI ISLAM DALAM KURIKULUM PERGURUAN TINGGI: MEKANISME, GOVERNANCE, DAN PEMBELAJARAN TRANSFORMATIF – SYSTEMATIC LITERATURE REVIEW - Patoni; Aries Rapelianto; Sany Rahmah Padilah; Yudi Prayitno; Ade Tutty R.Rosa; Agus Mulyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The integration of Islamic values in the higher education curriculum is a complex epistemological and institutional challenge that requires a systemic and thoughtful approach in the era of modern higher education that is increasingly global. This research aims to explore four main dimensions: (1) how Islamic values can be integrated without sacrificing academic rigor and international standards; (2) mechanisms that facilitate or hinder implementation in classroom learning and the role of academic agencies; (3) institutional governance, academic leadership, and stakeholder collaboration; and (4) contribution to transformative learning and ethical-spiritual development of students. The method used was a systematic literature review with the PRISMA 2020 protocol, analyzing 32 articles out of 121 articles screened, sourced from the Scopus database. The results show that effective integration requires simultaneous transformation at four levels of the organization (institutional, programmatic, pedagogical, and personal), strong academic agency with a sense of ownership, coordinated governance with adequate resource allocation, and active collaboration with religious communities. The integration of Islamic values can produce meaningful learning outcomes in employability, civic engagement, and citizenship development without sacrificing academic standards. In conclusion, the integration of Islamic values in the higher education curriculum is possible and beneficial when supported by a systemic approach, clear leadership, professional development of lecturers, and adequate allocation of resources.